2023
DOI: 10.1002/hsr2.1752
|View full text |Cite
|
Sign up to set email alerts
|

Methanol poisoning during the COVID‐19 pandemic in Iran: A retrospective cross‐sectional study of clinical, laboratory, and brain imaging characteristics and outcomes

Saeid Esmaeilian,
Arash Teimouri,
Sedighe Hooshmandi
et al.

Abstract: ObjectiveTo evaluate the frequency and significance of brain imaging findings in methanol poisoning patients and to propose a criterion for prioritizing brain imaging.MethodsWe retrospectively reviewed the data of 306 patients (286 men and 34 women, mean age 32.10 ± 9.9 years) with confirmed methanol poisoning who were admitted to two hospitals in Iran during the COVID‐19 pandemic. We analyzed their demographic, clinical, laboratory, and brain imaging data.ResultsThe main brain computed tomography (CT) scan fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Additionally, Esmaeilian et al demonstrated a significant correlation between being over the age of thirty and a history of blindness (75.9%) with a decreased chance of patient survival. Notably, these factors were not associated with abnormal findings in brain CT scans (26). Our findings align with these previous studies, highlighting consistent patterns of clinical outcomes following methanol poisoning.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, Esmaeilian et al demonstrated a significant correlation between being over the age of thirty and a history of blindness (75.9%) with a decreased chance of patient survival. Notably, these factors were not associated with abnormal findings in brain CT scans (26). Our findings align with these previous studies, highlighting consistent patterns of clinical outcomes following methanol poisoning.…”
Section: Discussionsupporting
confidence: 91%
“…Research supports the use of brain imaging as a crucial tool in identifying and managing patients with methanol poisoning. It is recommended that patients displaying severe acidosis and reduced levels of GCS, pH, and oxygen saturation, coupled with elevated glucose levels, should be prioritized for a brain CT scan (26). This approach helps in better understanding the extent of neurological damage and guiding appropriate treatment interventions.…”
Section: Risk Of Bias Within the Studiesmentioning
confidence: 99%